1990
DOI: 10.1007/bf00010751
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia volatilization from cattle slurry following surface application to grassland

Abstract: Three experiments were conducted to examine the influence of slurry application rate, wind speed and applying slurry in narrow bands on ammonia (NH3) volatilization from cattle slurry surface-applied to grassland. The experiments were conducted in the field using a system of small wind tunnels to measure NH 3 loss. There was an inverse relationship between slurry application rate and the proportion of NH4+-N volatilized. From slurry applied at 20, 40, 60, 80, 100 and 120 m 3 ha -1, the respective proportions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(21 citation statements)
references
References 18 publications
3
17
0
1
Order By: Relevance
“…Wind enhances diffusion by removing NH 3 from the applied surface, while at the same time keeping the NH 3 concentration in the air above the surface low. Brunke et al (1988), Thompson et al (1990) and found that losses increased with wind speeds of up to 2.5 m s (Fig. 3).…”
Section: A Bmentioning
confidence: 91%
“…Wind enhances diffusion by removing NH 3 from the applied surface, while at the same time keeping the NH 3 concentration in the air above the surface low. Brunke et al (1988), Thompson et al (1990) and found that losses increased with wind speeds of up to 2.5 m s (Fig. 3).…”
Section: A Bmentioning
confidence: 91%
“…Regardless of tillage treatment, the first 8 h after slurry application is the most crucial time in terms of NH 3 -N loss. Thompson, Pain, and Rees (1990) found that 57-77 percent of total NH 3 -N emission occurred in first 24 h. Similarly, Bitmann et al (2005) reported that 85 percent of NH 3 -N volatilized within 24 h with surface applied manure. They also reported that using aeration reduced NH 3 -N emissions by up to 52 percent compared with no incorporation.…”
Section: Ammonia Volatilizationmentioning
confidence: 92%
“…They found that there was a 1015% increase in total available N lost for every 1 m s −1 increase in wind speed following with pig and cattle manure application. Thompson et al (1990) also found a positive response to increased wind speed (0.5-3 m s −1 ) with surface-applied cattle slurry, but in their study, wind speed was not a dominant factor in overall ammonia losses. Sommer et al (1991) showed a positive increase in losses, from cattle slurry, up to 2.5 m s −1 , whereas increases in wind speed beyond 2.5-4 m s −1 did not influence loss.…”
Section: Wind Tunnel Designmentioning
confidence: 81%